The use of Lactic-Acid-Based Copolymer (LABC) as a dressing on split thickness skin grafts in partial and full thickness burn. Issue 2 (April 2022) - Navarro, Eduardo; Mazirka, Pavel; Thigpin, Tera; Carson, Joshua
Highlights: A synthetic copolymer dressing simulates the body's natural epithelium and has reported antiseptic properties. The synthetic dressing can be efficacious as a post-operative dressing for management of skin-graft donor sites. The synthetic dressing can also be successfully used to cover and support STSGs. The porous structure and a high degree of plasticity allows for wound shape adaptation. The synthetic dressing also allows wound examination without removal of the dressing. Abstract: Split-thickness skin grafting (STSG) is one of the most frequently used approaches to wound coverage in large size deep partial thickness and full thickness burns. The technique, however, is often degraded by partial, and at times complete, failure of graft to take. Though often multifactorial; operative technique, quality of wound bed and the type of dressing used are key factors in the ability of the STSG to heal. Various dressing methods have been described in the literature with varying benefits and degree of success but no consensus on a gold standard has been reached. This study describes the use of intra-operatively placed Lactic-Acid-Based Copolymer (LABC) as a dressing for meshed STSG and its impact on skin graft survival. A retrospective chart review of patients who received LABC dressing over their STSG was performed. A total of 22 patients, 16 male (73%) and 6 female (27%), with a mean age of 36.5 years, were included. Burn injuries were due to fire (10), grease (8), scald (2) and electrical (2), with a median treated area of 375 cm 2 and follow up ranging from 21 to 232 days. Complete wound healing with no graft loss was documented in 17 of 22 (77%) patients; with the remaining 5 patients being lost to follow up. Intraoperative LABC dressing application after split-thickness skin grafting in burn patients was shown to be an effective strategy in protecting the STSG site and allowing graft take.